VALUE SHIFTING AT MEUNASAH IN LANGSA IN SOCIAL CONTEXT - Cut Intan Meutia; Chery Julida Panjaitan; Fadhillah Wiandari (Jurnal Education and Development, 2022)
The purpose of this study is to explore the shifting atmeunasah in Langsa City. The shifting is seen from various aspects such as the architectural form and also the values​adopted in the existing meunasah. Although, there are still meunasah that have not been organized in a modern way, the meunasah are still running as usual in a patrilineal society tradition with a strong charismatic power. Thus, all activities are centered on the leader; in this case the tradition in Aceh, that isTeungku, namely Teungku Imum Meunasah. The research methodology uses a phenomenological and historical approach by using data collection tools in the form of observation, documentation and interviews. Then the data is interpreted by data reduction. To strengthen the final results, data cross-checks and triangulation are held, so that the data reached the maximum level. Based on the existing results, currently there are twelve meunasah buildings administratively recorded. All of these meunasah are located in Langsa and in terms of architecture and are multi-functional. The five meunasah are still original. Moreover, there are seven administrative meunasah as meunasah itself, but the shape and model is a Mushala building, and the administrators are Imum Gampong, Imum Dusun, Imum Hafiz, and Imum Rawatib.